Expansion of Natural Killer Cells in Peripheral Blood in a Japanese Elderly with Human T-Cell Lymphotropic Virus Type 1-Related Skin Lesions - Shinsaku Imashuku; Naoko Kudo; Kagekatsu Kubo; Kouichi Ohshima (Case Reports in Dermatological Medicine)
Natural killer (NK) cells were proposed to play an important role in the pathogenesis of human T-cell lymphotropic virus type 1- (HTLV-1-) associated neurologic disease. Our patient was a 77-year-old Japanese man, who had been treated for infective dermatitis associated with HTLV-1 for nearly 10 years. When referred to us, he had facial eczema/edema as well as extensive dermatitis at the neck/upper chest and nuchal area/upper back regions. Dermal lesions had CD3+CD4+ cells, but no NK cells. Flow cytometry of his peripheral blood showed a phenotype of CD2+ (97%), CD3+ (17%), CD4+ (12%), CD7+ (94%), CD8+ (6%), CD11c+ (70%), CD16+ (82%), CD19+ (0%), CD20+ (0%), CD56+ (67%), HLA-DR+ (68%), and NKp46+ (36%). Absolute numbers of CD56+NK cells in the peripheral blood were in a range of 986/μL–1,270/μL. The expanded NK cells in the peripheral blood are considered to be reactive, to maintain the confinement of the HTLV-1-positive CD4+ cells in the skin, and to prevent the progression of the disease.